Rights of an arrested person to counsel: is it not a case of too little too late? - Kamarudin, Abdul Rani (2005)
This paper proposes to determine whether an arrested person has access to a legal counsel whilst under police custody immediately after he has been arrested. In Malaysia, the right to counsel is a constitutional right. This right to counsel also correlates to his right to remain silent during interrogation, and the right against any inducement, treat or promise in relation to the charge against him. It becomes necessary then to discuss as to how long might an arrested person be detained in police custody since the computation of time for the first 24 hours does not include weekly holiday and public holiday. It is submitted that the police are empowered to detain an arrested person for 24 hours, and that an extension of that time granted by Magistrates, must, it is assumed to allow the police to complete their investigation. This bring into issue that if counsel is only allowed after the police are done with their investigation (interrogation), would it not then be a case of too little too late since the arrested person would not know of his rights and would through ignorance, stupidity or helplessness by reason of the detention have made damaging statements to the Police. Thus, this paper evaluates the current legal position in that person arrested and under lawful custody may be denied legal counsel, if by allowing that hinders police investigation.